Podor v južni steni Punta Thurwieser (Italija) 18. septembra 2004 - Rozman, Janez (Geologija, 2004)
Photos and short description of a large rockfall in the south rock wall of Punta Thurwieser - 3657 m - in the Ortler group are presented. They belong to the very rare authentic documents of geological events reshaping the current topography of the Alps.
Keywords: Alpe; Alps; Italija; Italy; podori